Retention of knowledge on blood pressure measurement among medical students within preparation for primary accreditation - A. S. Klimenko; A. I. Badretdinova; Zh. G. Tigay; I. D. Dzhopua; I. S. Nikitin; R. V. Tania; D. Yu. Ovsyannikov (Российский кардиологический журнал, 2021)
Aim. To assess the retained knowledge of sixth year medical students on noninvasive blood pressure (BP) measurement.Material and methods. The study included 148 6th year medical students. According to the curriculum, in the fall semester, students studied the procedure of BP measurement according to checklists developed based on ROSOMED. In the spring semester, as part of the preparation course for accreditation, the retained knowledge of students was assessed. A completed skill was assessed at 1 point, not completed — 0 points. Thus, each student can score a maximum of 50 points. The teacher assessed the manipulations during their performing by filling in the checklist items for each student.Results. None of the students completed the full range of manipulations. The number of completed skills ranged from 15 (30%) to 49 (98%) and averaged 33 points on the checklist (66%). In addition, 74% of students (n=109) completed more than half of the required skills. Almost the only item completed by all students (99%, n=146) was a greeting, which was comparable with self-presentation (92%, n=136) and identification of a patient’s personal data (surname and first names) (80%, n=118). The rest of checklist items was performed in the range from 39% (n=57) for “remeasurement of BP on the other hand” to 87% (n=129) for “finding a radial pulse”. Thus, the average fulfillment rate was 67% (n=99). There were following most common mistakes in BP measurement: 39% of students did not measure a patient’s upper arm diameter and did not select the cuff size; every second student (51%) placed the phonendoscope diaphragm under the cuff; 40% of students reduced the cuff pressure with inadequate rate.Conclusion. The retention of knowledge on measuring BP within six months after a detailed analysis and passing a test remains insufficient, but comparable with foreign studies. The data obtained indicate the need for additional trainings both using simulators and in conditions closer to real ones, including with simulated patients.